Elbow Dislocation and Subluxation Injuries in the National Collegiate Athletic Association, 2009-2010 Through 2013-2014 - Goodman, Avi D. (Orthop J Sports Med, 2018)
BACKGROUND: Examination of the incidence of elbow dislocation and subluxation injuries in the collegiate athlete population is limited. PURPOSE: To determine the incidence of elbow dislocation and subluxation injuries in the National Collegiate Athletic Association (NCAA) and investigate the risk factors involved. STUDY DESIGN: Descriptive epidemiology study. METHODS: All elbow subluxation and dislocation injuries from the 2009-2010 through 2013-2014 academic years in the NCAA Injury Surveillance Program database were extracted. The incidence was calculated for different injuries, sports, activity, time in game, competition status, and injury characteristics. Such differences were compared by use of risk ratios to determine risk factors for injury. RESULTS: The overall incidence of elbow instability injuries was 0.04 per 10,000 athlete-exposures (AEs). Elbow dislocations were more common, with 553 injuries (82.2%, 0.03/10,000 AEs), while elbow subluxations were the minority, with 119 injuries (17.8%, 0.01/10,000 AEs). Men’s wrestling had the highest incidence of elbow instability (1.08/10,000 AEs), more than women’s gymnastics (0.74), men’s football (0.11), and women’s volleyball (0.06). All injuries occurred via a contact mechanism, and 99.2% were new injuries. Sixty-nine percent of injuries kept athletes sidelined for more than 2 weeks. Injuries were 3 times more likely to occur in competition (0.08/10,000 AEs) than practice (0.03/10,000 AEs). Injuries sustained during competition were 1.4 times more likely to occur early in the match than late. CONCLUSION: Elbow instability injuries are an infrequent but serious source of disability for select NCAA athletes, with a number of associated risk factors. Athletes sustaining these injuries, along with their coaches and medical providers, may benefit from these return-to-play data to best manage expectations and outcomes.